Impacts on the right to an early rural-urban childhood education - Marín Posada, Mary Luz; Saldarriaga Velez, Jaime Alberto; Urrea Parra, Yohanna; Morales Montoya, Carolina (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2022)
This following article is the result of the investigation named El derecho a la educación de los niños y las niñas de primera infancia de la vereda La Aldea de San Sebastián de Palmitas, 2021. It is based on a lecture in critical hermeneutical reading that studies the effects of the right to education for girls and boys in the early childhood from a rural-urban area of ​​Medellín, Colombia's second city. The research was conducted during the times of the Covid-19 pandemic, allowing a greater visibility of the disadvantages that exist for the girls and boys from the rural-urban early childhood country (0-6 years), studying it from a perspective of the right to education and rights in education, being aware of its drawback with the urban people. Furthermore, the voices of the boys, girls, mothers and fathers, the educators, and the community- and government leaders were taken for research purposes. Applying as a conceptual reference the indicators of the right to education proposed by UNESCO, the words affordability, accessibility, acceptability and adaptability reveals how the right to a rural-urban early childhood education is being implemented in a restricted way, which in the case of the village La Aldea, it goes as far as it reaches its derealization. To that end, there is a search for a way to be able to contribute to the fight for a recognition of the right to early childhood education in rural and rural-urban territories by revealing the ignorance of the territorial diversity, of the girls and boys as subjects of rights and social actors and their needs and specific interests, and of themselves in terms of their status as subjects of rights.